Experiences and influences of grief processing in the treatment of an individual with spinal cord injury - Eraldo Cordeiro Rabelo; Sandra das Dores Souza; Elizângela Ferreira Silva (Estudos de Psicologia (Campinas))
Abstract Objective The study reports a case of a person who suffered a spinal cord injury called Trauma Raquio Medular. The question was answered: can the grief of the patient, his/her family and the professionals contribute or hinder treatment and rehabilitation? Method The medical records of a patient treated at an Emergency Hospital were analyzed. The analyses will be based on psychological theories about grief with complements from psychoanalysis, seeking to report from the psychologist’s perspective the experiences of grief in hospital treatment. Results This clinical case was chosen due to the complex history in biopsychosocial aspects of the patient. The body in its fragility can be modified by traumatic situations, such as: amputations, spinal and head injuries, among others. From the bodily changes, grief can be experienced. Conclusion Understanding the grief process can provide more effective and humanized care, with a view to returning to the territory.